The effects of the early intake of omega 3 in the prevention of obesity and cardiovascular diseases - Ribeiro, Emanuella Alves (2022)
Since the Paleolithic Era, humanity has already presented different eating behaviors and health habits, however, the prevalence of counterproductive attitudes of the populations has never reached such alarming proportions as at the present time, providing, as a consequence of this lifestyle adopted individually and collectively, , significant cases of obesity, dyslipidemia, cardiovascular diseases, among other Chronic Non-Communicable Diseases (NCDs), which entered the list of risk for the health of the organism. In view of this, the present research refers to the effects of early intake of omega 3 in the prevention of obesity and cardiovascular diseases, addressing the relevant mechanisms of action of these n-3 polyunsaturated fatty acids (n-3 PUFAs) in body cells. human, its interaction with other metabolic reactions of the body and the association of the consumption of these essential fats with the prevention of pro-inflammatory disorders and as an auxiliary factor for the improvement of clinical cases of heart disease, especially coronary artery disease, and obesity. It consists of a literature review, based on the cognitive approach of scientific analysis, using about 29 studies, including scientific articles and textbooks, capable of supporting the metabolic processes of omega-3, using the terms: omega-3, chronic diseases non-communicable diseases, inflammation, obesity and cardiovascular disease. In view of the results found, it is possible to establish a correlation between the beneficial effects of omega-3 consumption with the improvement of hypertriglyceridemic modulation, which led to the perception that the etiology, which we have control over, for such pathologies mentioned is strongly linked to the history individual and collective lifestyle.